1976
DOI: 10.1530/jrf.0.0460359
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of blood flow to the reproductive organs of rats near term

Abstract: The rate of ovarian and utero-placental blood flow through vessels of less than 25 mum diameter was examined with radioactive microspheres in 5 non-pregnant rats and 19 rats at Day 22 of pregnancy. Total blood flow to the reproductive organs was 0-559 ml/min in the non-pregnant animals and 13-2 ml/min in those near term, a 23-fold difference. The mean ovarian blood flow was high and increased from 0-202 ml/min to 0-845 ml/min. Myometrial and endometrial blood flow increased from 0-156 to 2-24 ml/min. The mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
37
0

Year Published

1977
1977
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 10 publications
(6 reference statements)
8
37
0
Order By: Relevance
“…The blood flow per placenta of the N fetuses, 0.50-0.95 ml/rnin, was in the range of previously reported flow rates of rats in late gestation (2,3,5,IS,16,21,29,34). Also, our values of renal blood flow and pulmonary blood flow are in agreement with those found in previous investigations (20,31).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The blood flow per placenta of the N fetuses, 0.50-0.95 ml/rnin, was in the range of previously reported flow rates of rats in late gestation (2,3,5,IS,16,21,29,34). Also, our values of renal blood flow and pulmonary blood flow are in agreement with those found in previous investigations (20,31).…”
Section: Resultssupporting
confidence: 92%
“…Although a number of estimations of placental blood flow in rodents have been reported (I , 2,5,7,15,16,27,29,34), no studies of placental blood flow in diabetic rat pregnancy seem to have been published. There are, however, reports of altered placental morphology (26) and indirect evidences of changed vascular function in diabetic rat placenta (4) as well as decreased transfer of aminoisobutyric acid to fetuses ofdiabetic guinea pigs (30).…”
Section: Discussionmentioning
confidence: 99%
“…While numerous studies (6,9,10,17,24,47) have reported various effects and gestational timing of increased unilateral or bilateral uterine artery resistance, to our knowledge, none have specifically reported the different effects of timing (from days 12-17, and days 14 -19 of gestation) of ischemic induction and maternal blood pressure and angiogenic balance in the gravid When fetal weight is plotted relative to uterine position (ordered from ovarian to cervical), there are profound treatment (RUPP vs. NP) and timing (d17 vs. d19) differences in fetal size in late gestation. While the slopes of the fetal size relative to uterine position curve were different between d17 and d19 rats ( †P Ͻ 0.05), only in the d19 rats was a treatment effect observed (*P Ͻ 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…The flow fraction to the maternal side of the placenta was 34-5 +11-2 % (n = 5). At a pump rate of 2 ml min-' the corresponding flow rate is about 0 7 ml min-', which is equal to the maternal placental blood flow in the rat near to term (0-7 ml min-'; Bruce, 1976 (Fig. 3).…”
Section: Goeneral Observationsmentioning
confidence: 91%